Annealing of indium tin oxide (ITO) coated optical fibers for optical and electrochemical sensing purposes - Dominik, M.; Swatowska, Barbara; Siuzdak, K.; Maziarz, Wojciech; Niedziałkowski, P.; Pisarkiewicz, Tadeusz; Straňák, Vítězslav; Kucewicz, Wojciech; Sezemský, Petr; Sobaszek, M.; Bogdanowicz, R.; Ossowski, T.; et al. (Society of Photo-optical Instrumentation Engineers, 2016)
Glass and fiber structures with Indium Tin Oxide (ITO) coating were subjected to annealing in order to identify impact of the thermal treatment on their optical and electrochemical properties. It is shown that the annealing process significantly modifies optical properties and thickness of the films, which are crucial for performance of optical fiber sensors. Moreover, it visibly improves electrochemical activity of ITO on glass slides and thicker (Ø=400 μm) ITO-coated fibers, whereas in the case of thinner fibers (Ø=125 μm) it could lead to a loss of their electrochemical activity. Depending on the applied substrate and the annealing process, the investigated structures with ITO coating can be further used as fiber-based sensors with integrated opto-electrochemical readout.
Keywords: electrochemical sensing; fiber optic sensor; indium tin oxide (ITO); optical properties; thermal annealing